体外循環を用いる開心術における血液節減と術後肝炎。特に自家血輸血及び人工じんによる回路残留血再利用の評価 - NOBUOKA W.; YOKOYAMA S.; KONISI M.; ASAZUMA S. (Jinko Zoki, 1984)
Postoperative hepatitis has been increasing since blood components transfusion utilised. We investigated on 184 patients undergone open-heart operation using cardiopulmonary bypass. One hundred and thirty-four patients received only blood components and 50 patients received whole blood. The incidence of postoperative hepatitis was 20% (20) in blood components group and 10% (5) in whole blood group. The counterplan to prevent postoperative hepatitis was presented by the authors. Transfusion with autologous blood, washed red cells and albumin derivatives was proposed. To conserve blood during cardiac surgery, we concentrated diluted blood remained in the pump oxygenator using hallow fiber artificial kidney (HFAK) and returned them to each patients operated by autotransfusion methods. By using this method, we could undergo the open heart operation with as only 1% homologous blood volume as blood components group, and the incidense of post operative hepatitis we got was 1/38. 成分輸血療法の普及に伴い, 術後肝炎の増加が注目されている。我々が1977年7月から1983年2月迄に行った心臓手術症例の中の開心術のうちfollow出来た。成分輸血療法で行った開心術の術後肝炎は134例中28例であり, 全血使用群の50例中5例の2倍である。この原因には輸注donor数の増加が関係しており, 術後肝炎発生防止の対策としてautotransfusionを併用する洗浄赤血球とアルブミンを用いる方法によって開心術の全経過を行っている。この方法で行った症例は38例で肝炎は1例のみである。自家血群では血液使用量が節減されるが,この方法に人工腎を用いて人工心肺残留液の濃縮再輸血を併用すると成分輸血群の同種血液使用量の約4分の1で充分であった。